The Effect of Service Quality And Price on Customer Satisfaction Through Product Quality (Case study of Kavez Coffee) - Achmad Fahri; Wagiarto Hoesin; Eddy Sanusi P Silitonga (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2023)
This study aims to analyze service quality and price on customer satisfaction through product quality, analyze service quality and prices on customer satisfaction, analyze the effect of product quality on customer satisfaction, analyze the indirect effect of service and price on customer satisfaction through product quality and analyze the effect of non direct service quality and price to customer satisfaction. The research was conducted at Kavez Coffee involving 30 people. The research sample was taken using probability sampling and simple random sampling. Data analysis using path analysis. Based on data analysis, it is known that there is a direct effect of service quality on customer satisfaction and a direct effect of price on customer satisfaction at Kavez Coffee. Then the results of the analysis of the product quality variable as an intervening variable can be perfectly proven, namely the product variable has an indirect effect on the service quality variable on customer satisfaction and the price variable on customer satisfaction. This statement can be proven by the magnitude of the indirect effect (service quality on customer satisfaction and price on customer satisfaction) through product quality which is identified as an intervening variable